Аудит фінансової звітності: стратегія, план, процедури та методи - Колісник, Олена Пилипівна; Шацков, Віктор Володимирович (Видавничий дім «Гельветика», 2024)
Метою статті є дослідження порядку складання загального плану та розробки програми аудиту фінансової звітності з відповідними аудиторськими процедурами та аналітичними методами. Серед загальнонаукових методів, використаних для досягнення мети статті, використовувалися: синтез – при дослідженні складання загального плану та розробки програми аудиту фінансової звітності, аналіз – при дослідженні аудиторських процедур та аналітичних методів аудиту фінансової звітності, логічний метод – при побудові результатів дослідження. Розглянуто загальні цілі аудитора під час перевірки фінансової звітності. Виділено чотири основні етапи процесу аудиту фінансової звітності: формулювання завдання, оцінка ризиків, тестування, завершальні процедури. Досліджено фактори та порядок визначення суттєвих рахунків і додатків, а також їхні відповідні судження. Визначено мету стратегії аудиту та описано складові плану аудиту. Розглянуто види аудиторських процедур і аналітичних методів, а також розроблено додаткові довідники щодо порядку їх використання на різних етапах процесу аудиту фінансової звітності. Визначено результати аудиторської перевірки фінансової звітності, на основі яких формується аудиторська думка. Використання результатів дослідження допоможе забезпечити здійснення ефективного аудиту фінансової звітності відповідно до вимог міжнародних стандартів.

Many companies are switching to drawing up financial statements in accordance with international standards, which are audited by independent auditors. At the same time, the specificity of business entities' activities and the growing complexity of their business processes challenge auditors to ensure the credibility and reliability of audit procedures for verifying financial statements. This affects the fact that many questions arise regarding how to ensure the implementation of an effective audit of financial statements in accordance with the requirements of International Standards. The purpose of the article is to study of preparing a financial statement audit program with appropriate audit procedures and analytical methods. Among the general scientific methods used to achieve the goal of the article, the following were used: synthesis – in the study of the preparation of the general plan and development of the financial statement audit program, analysis – in the study of audit procedures and analytical methods of financial statement audit, logical method – in the construction of research results. The general objectives of the auditor during the financial statement audit are considered. There are four main stages of financial statement audit process: formulation of the task, risk assessment, testing, final procedures. Factors and order of determining significant accounts and applications and their respective judgments were studied. The purpose of the audit strategy is defined and the components of the audit plan are described. Types of audit procedures and analytical methods were considered, and additional guides were developed on the order of their use at various stages of the financial statement audit process. The results of the financial statement audit, on the basis of which the auditor's opinion is formed, are defined. Using the results of the study will help ensure an effective audit of financial statements. in accordance with the requirements of International Standards on Auditing and International Financial Reporting Standards.
Keywords: аудит; фінансова звітність; аудиторські процедури; аналітичні методи; оцінка ризиків; тестування; аudit; financial statement; audit procedures; analytical methods; risk assessment; testing